Engaging with undergraduate geography students' perspectives on the value of geography to a person's education. (2nd September 2022) - Hammond, Lauren; Healy, Grace
ABSTRACT: In this article, we explore perspectives on, and experiences of, geography education, by engaging with those looking at the ﬁeld from a different vantage point than those working in it – those studying geography. The article begins by examining the importance of student voice in and to geography education, before drawing on a survey of 333 undergraduate geography students from across the British Isles conducted in late 2020. Through engaging with student perspectives, we contribute to discussions about the value of geography to a person's education. We conclude by arguing for both the importance of educators truly valuing students' perspectives and experiences, and institutional mechanisms that support and empower geography educators in their practices in this regard.